一种用于大型空间飞行器地面振动试验夹具 (2019)
本发明提供了一种用于大型空间飞行器地面振动试验夹具，该夹具采用柱状结构，以将试验产品的接口由横向转化为纵向，夹具采用分体形式，包括上夹具和下夹具，以减轻夹具的重量，夹具的一阶共振频率为220Hz。本发明夹具结构强度高、刚度大、承载能力强、响应均匀，解决了大型振动试验夹具设计的技术难点，制造成本低、适用性强，取得了良好的经济效应。 The invention provides a ground vibration test clamp used for a large-scale spacecraft. The clamp adopts a cylindrical structure, and is used to switch an interface of a tested product from a horizontal direction to a vertical direction. The clamp adopts a split form, and comprises an upper clamp and a lower clamp, and the weight of the clamp is reduced, and the first order resonant frequency of the clamp is 220 Hz. The ground vibration test clamp has advantages of high structural strength, large rigidity, strong bearing capability, uniform response, low production costs, strong adaptability, and abilities of solving technical difficulties of design of large-scale vibration test clamp and achieving good economic effect.